ANALISIS KANDUNGAN BAKTERI ESCHERECIA COLI PADA MINUMAN ES CENDOL DI PASAR KODIM KOTA PEKANBARU TAHUN 2017 - Yessi Harnani; Fahrur Rozie (EcoNews, 2018)
Es cendol is a product of non-packaged beverages that are in great demand by the public. Es cendol has the potential as a source of disease transmission if in the process of processing, storage, presentation is not true The purpose of this research is to know the presence or absence of E. Coli bacteria and description of knowledge of handlers, water sources, personal hygiene, sanitary conditions and cendol beverage equipment. This research is qualitative analytic. The subject of the research is the seller of ice cendol with sample of 8 samples from 4 traders. The instrument of this study is self-study which is assisted by in-depth interview guides, observation sheets, documents related to voice recorder, camera and laboratory analysis. The results showed there are related variables. Researchers analyzed the content of E. coli bacteria on cendol ice drink at UPT (Technical Implementation Unit) Pekanbaru Health and Environmental Laboratory in May 2017. The result of this research showed that E. Coli bacteria in sample 6 and sample 8 were 16/100 ml, and 1, 2, 3, 4, 5 and 7 samples were 240/100 ml. This is not in accordance with Kepmenkes RI No.492/Menkes/PER/IV/2010 that the Microbiological Requirements for drinking water is 0/100 ml of sample. It is expected that BPOM Riau Province and City Health Office Pekanbaru more monitor and act again to improve efforts in health especially on making ice cendol drinks at Pekanbaru Municipal Market Military City against Escherichia coli bacteria.